2011
DOI: 10.2527/jas.2010-3302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary energy level and ractopamine on growth performance, carcass characteristics, and meat quality of finishing pigs

Abstract: A total of 54 finishing barrows (initial BW = 99.8 ± 5.1 kg; PIC C22 × 337) reared in individual pens were allotted to 1 of 6 dietary treatments in a 2 × 3 factorial arrangement of treatments with 2 levels of ractopamine (0 and 7.4 mg/kg) and 3 levels of dietary energy (high, 3,537; medium, 3,369; and low, 3,317 kcal of ME/kg) to determine the effects of dietary ractopamine and various energy levels on growth performance, carcass characteristics, and meat quality of finishing pigs. High-energy diets were corn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
35
1
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 20 publications
14
35
1
12
Order By: Relevance
“…As medidas de pH foram realizadas em 1 e 24h após o abate (BRIDI et al, 2003;HINSON et al, 2011), a partir de amostra de pernil (Semimembranosus), utilizando pHmetro com eletrodo de inserção (pH 320/Ste-1, WTW). Foram realizadas 5 coletas e a análise realizada em triplicata para cada tratamento.…”
Section: Methodsunclassified
See 2 more Smart Citations
“…As medidas de pH foram realizadas em 1 e 24h após o abate (BRIDI et al, 2003;HINSON et al, 2011), a partir de amostra de pernil (Semimembranosus), utilizando pHmetro com eletrodo de inserção (pH 320/Ste-1, WTW). Foram realizadas 5 coletas e a análise realizada em triplicata para cada tratamento.…”
Section: Methodsunclassified
“…O pH mais elevado, observado no tratamento com Ractopamina, pode estar relacionado à redução das reservas de glicogênio do animal, devido à agitação e estresse dos suínos na propriedade em momento anterior ao abate (visto que o transporte de todos os animais foi realizado sob as mesmas normas), estando de acordo com os dados publicados por POLETTO et al (2010), HINSON et al (2011), quando foi constatado que suínos alimentados com ractopamina se tornam mais agressivos, o que pode ser a causa de estresse na propriedade.…”
Section: ±095 ------------------------------------------------------unclassified
See 1 more Smart Citation
“…This absence of effect may be related to the range of body weights (70-100kg) in the experimental period, as prior research has demonstrated the benefits of ractopamine addition to the diets of pigs weighing over 100kg at slaughter time, particularly in terms of weight gain (CORASSA et al, 2009) and feed conversion (ALMEIDA et al, 2010). Genotypic features may be another reason why ractopamine did not affect performance, since variability in the genetic materials employed in different studies may affect the variables evaluated (HINSON et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…No caso de intervenções ante mortem, o fornecimento de ractopamina nas dietas e sua relação no post mortem com a redução ou aumento das perdas de água por exsudação (drip loss e cocção) na qualidade da carne foi demonstrada em investigações científicas (UTTARO et al, 1993;HINSON et al, 2014;JEONG et al, 2011;LEAL et al, 2014).…”
Section: Perfil Proteico Da Carne In Naturaunclassified